Obsessive Compulsive Symptoms Predict Posttraumatic Growth: A Longitudinal Study. Issue 6 (1st November 2016) - Mamon, Daria; Solomon, Zahava; Dekel, Sharon
ABSTRACT: Although posttraumatic growth (PTG) has received growing attention, the relationship between PTG and distress remains unclear. This longitudinal study examines the relationship between posttraumatic obsessive-compulsive (OC) symptoms and PTG. Israeli veterans were followed over 17 years using self-report questionnaires of OC symptoms, posttraumatic stress disorder (PTSD), and PTG. Hierarchical regression analyses demonstrated that OC symptoms predicted PTG, even when initial PTG levels and PTSD symptoms were controlled for in the combatants group. These preliminary findings suggest that OC symptoms may play an important role in facilitating psychological growth. Future research is warranted to explore the mechanisms responsible for this relationship.